Characterization of Mortality due to Malignant Tumors - María del Carmen Rodríguez Velázquez; Zoraida Vivar Rivas; Yoenny Peña García; Dolys Suárez Padilla; Alberto Caballero Laguna (Revista Finlay)
Foundation: cancer is one of the first 20 causes of premature death in women and men worldwide. In 2012 it was estimated that more than 4 million people suffered from cancer and more than 8,2 million died for this cause. Objective: to characterize mortality due to malignant tumors in the Puerto Padre Municipality from 2014 to 2018. Method: a retrospective descriptive study was conducted. The information was processed by rates and percentages calculation. For better comprehension and posterior analysis, distribution and frequency tables and charts were design. Results: deceased aged 75 or more prevailed. In the female sex, 5 967 years were lost with respect to the male one 5 642 years, in the municipality 126,2 years were lost due to malignant tumors every thousand inhabitants. Deaths were more frequent in urban zones. The highest rate was found in the Rafael Izquierdo health area (11,43), it exceeds the municipal rate (11,36). The most common malignant tumors in the male sex were: lung, prostate, and esophagus and the in the female: lung, breast, and colon. In general, the most frequent locations were: lung, prostate, colon, breast, and esophagus. Conclusion: mortality trend due to malignant tumors in the five-year period from 2014-2018 was descending, there was an over male mortality, however more years of life were lost in the female population. The Rafael Izquierdo health area was identified as of a high risk and the main locations were: lung, prostate, colon, breast and esophagus.